2021
DOI: 10.1039/d0ra07198f
|View full text |Cite
|
Sign up to set email alerts
|

Cellulose nanocrystal assisted trace silver nitrate to synthesize green silver nanocomposites with antibacterial activity

Abstract: Cellulose nanocrystals (CNCs) with silver nanoparticles (AgNPs) are used for applications ranging from chemical catalysis to environmental remediation, and generation of smart electronics and biological medicine such as antibacterial agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 70 publications
0
7
0
Order By: Relevance
“…In the XRD spectra (Figure b), the AgNC-CNC film displayed the same peak positions of cellulose as the CNC film, and three typical diffraction peaks appeared at 14.8° (110̅), 16.4° (110), and 22.6° (200) for the CNCs, which corresponded to cellulose I . Four new diffraction peaks at Bragg angles of 38.02°, 44.02°, 64.54°, and 77.40° were also observed for the AgNC-CNC film, corresponding to the reflections of the (111), (200), (220), and (311) crystalline planes of the fcc structure of Ag . The formation of AgNCs was further investigated by X-ray photoelectron spectroscopy (XPS), as shown in Figure c.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…In the XRD spectra (Figure b), the AgNC-CNC film displayed the same peak positions of cellulose as the CNC film, and three typical diffraction peaks appeared at 14.8° (110̅), 16.4° (110), and 22.6° (200) for the CNCs, which corresponded to cellulose I . Four new diffraction peaks at Bragg angles of 38.02°, 44.02°, 64.54°, and 77.40° were also observed for the AgNC-CNC film, corresponding to the reflections of the (111), (200), (220), and (311) crystalline planes of the fcc structure of Ag . The formation of AgNCs was further investigated by X-ray photoelectron spectroscopy (XPS), as shown in Figure c.…”
Section: Resultsmentioning
confidence: 88%
“…42 Four new diffraction peaks at Bragg angles of 38.02°, 44.02°, 64.54°, and 77.40°were also observed for the AgNC-CNC film, corresponding to the reflections of the (111), ( 200), (220), and (311) crystalline planes of the fcc structure of Ag. 54 The formation of AgNCs was further investigated by X-ray photoelectron spectroscopy (XPS), as shown in Figure 3c. The high-resolution XPS spectrum (Figure 3d) showed that two distinct peaks at 373.4 and 367.4 eV were identified to be the binding energies of the 3d 3/2 and 3d 5/2 electrons of Ag(0) and Ag(I), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…3F), the peak located at a binding energy of 368.9 eV was attributed to Ag 3d 5/2 while the peak located at a binding energy of 374.9 eV was attributed to Ag 3d 3/2 . The 6.0 eV binding energy separating this couplet is indicative of the presence of metallic silver 61,62 in the CNC/Ag hybrid material.…”
Section: Resultsmentioning
confidence: 99%
“…X-ray photoelectron spectroscopy survey of the coating in Figure 4(a) exhibited the main peaks of C 1s (283.5 eV) and O 1s (530.68 eV), as well as peak of N 1s (398.5 eV) which indicated the N-C bond from PVP. 56,57 The high-resolution spectrum in Figure 4(b) exhibited three different peaks with Si 2s (167.0 eV), Si 2p (101.1 eV), and S 2p (152.1 eV) which might come from the original latex urinary catheter layer, 58 as shown in Figure S1(f). The high-resolution C 1s spectrum of the coating could be fitted to three peaks at 283.3 eV (C1s-1 in Figure 4(c), similarly hereinafter), 284.4 eV (C1s-3), and 285.6 eV (C1s-2), which were assigned to C-OR, C-C, and C-O species, respectively.…”
Section: Resultsmentioning
confidence: 99%